Pemikiran Teologi AshâArÃ®yah dalam Irshâd al-âAql al-Salîm ilâ Mazâyâ al-Kitâb al-Karîm Karya Abû al-Suâud - Mubarok, Husni (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
This article explores theological thought of al-AshâarÃ® in Abû al-SuâÃ»dâs work Irshâd al-âAql al-Salîm ilâ Mazâyâ al-Kitâb al-Karîm. The study finds an interesting fact that when interpreting the Quranic verses on theological matters, Abû al-SuâÃ»d tended to affiliate to AshâarÃ®yah. However, Abû al-SuâÃ»d firmly stated that he referred most to al-Kashshâf of al-Zamakhsharî in his exegetical works. It has been widely known that al-Zamakhsharî was one of prominent proponents of Muâtazilah. The article emphasizes a number of theological issues discussed by Abû al-SuâÃ»d in his tafsîr such as Godâs free will, anthropomorphism, and Godâs justice. There have been three steps to analyze theological thoughts of AshâarÃ®yah mentioned in Abû al-SuâÃ»dâs work, are: firstly, grouping the most Quranic verses on theological realm referred by mutakallimîn. Secondly, explaining the views of each school (madhhab) of Islamic theology. Thirdly, discussing the assessments and interpretation of Abû al-SuâÃ»d on theological verses and comparing them to al-ZamakhsharÃ®âs interpretation. Based on these three steps the author will analyze the AshâarÃ®yah theological pattern adhered by Abû al-SuâÃ»d.